Copper-zinc alloy catalyst and its preparation method and application
By using copper-zinc alloy catalyst and using the CuZn alloy phase as the catalytic active site, the problem of copper alloy catalysts in the prior art requires support and additives, and efficient low-carbon alcohol synthesis is achieved, and good industrial prospects are provided.
Patent Information
- Application Number
- CN202311091983.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-29
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2043-08-29
AI Technical Summary
In the prior art, copper alloy catalysts require support and additives, resulting in high costs and difficult to separate products. Co's carbon chain growth capacity makes products widely distributed and difficult to achieve industrialization.
The copper-zinc alloy catalyst is used, and the CuZn alloy phase is used as the catalytic active site to expand the specific surface area of the particles, improve the catalytic performance, and achieve good catalytic effect without support and additives.
It has achieved that without the need for carriers and additives, the CO conversion rate reaches 20.86%, and the C2+ alcohol selectivity reaches 62.78%, with good catalytic effect and C2+ alcohol selectivity, and has better industrial prospects.
Smart Images

Figure CN117101666B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts, and in particular to a copper-zinc alloy catalyst and a preparation method and application thereof. Background Art
[0002] Low carbon alcohol refers to C 1-6 Mixed alcohols are often used as additives for fuel or clean gasoline. They mainly increase the oxygen content and improve the octane number of the fuel, thereby promoting clean combustion of the fuel. The most important thing for synthesizing low-carbon alcohols from syngas is to develop high-C 2+ Alcohol-selective catalysts. Currently, there are four main categories of catalysts for synthesizing low-carbon alcohols: Rh-based catalysts, Mo-based catalysts, modified FT catalysts, and modified methanol synthesis catalysts. Rh-based catalysts have mild reaction conditions and high selectivity for low-carbon alcohols, but Rh is a precious metal and is expensive, which is not conducive to industrialization; Mo-based catalysts are resistant to sulfur and not prone to carbon deposition, but the reaction conditions are harsh and the sulfides in the product are difficult to remove; modified FT synthesis catalysts have strong carbon chain growth capabilities, but the product distribution is wide and difficult to separate; modified methanol catalysts are mainly modified high-temperature Zn-Cr catalysts and modified low-temperature Cu-based catalysts. The reaction temperature and pressure of modified Zn-Cr catalysts are both high, resulting in high energy consumption and difficulty in industrialization. Modified Cu-based catalysts are low-cost, mild reaction conditions, and easier to industrialize, but the low-carbon alcohol yield of modified Cu-based catalysts is relatively low.
[0003] At present, the research on copper alloy as catalyst is mainly focused on CuCo bimetallic alloy catalyst, and in the prior art, using CuCo bimetallic alloy as catalyst requires carrier and other auxiliary agents (such as La2O3) on the one hand, and the carrier and auxiliary agent interact and block each other to promote the dispersion of CuCo alloy, thereby improving the activity of the catalyst to achieve catalytic synthesis gas to low-carbon alcohol; on the other hand, Co belongs to FT element and has strong carbon chain growth ability, so the product is difficult to separate, and the added auxiliary agent belongs to rare earth metal oxide, which is costly and not conducive to industrialization. Therefore, providing a copper alloy catalyst without adding any auxiliary agent and carrier, so that it can achieve good catalytic synthesis gas to low-carbon alcohol effect, has become a technical problem to be solved in the field. Summary of the invention
[0004] The purpose of the present invention is to provide a copper-zinc alloy catalyst and a preparation method and application thereof. The copper-zinc alloy catalyst provided by the present invention can achieve a good effect of catalyzing synthesis gas to prepare low-carbon alcohols without adding any auxiliary agent and carrier, and only using the copper-zinc alloy.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a copper-zinc alloy catalyst, comprising the following steps:
[0007] Pre-treating the copper-zinc alloy particles to obtain a copper-zinc alloy catalyst;
[0008] Alternatively, the copper-zinc alloy particles are pretreated and then partially dezincified to obtain a copper-zinc alloy catalyst.
[0009] Preferably, the copper-zinc alloy particles are made of brass.
[0010] Preferably, the pretreatment comprises: sequentially subjecting the copper-zinc alloy particles to ultrasonic cleaning with an organic solvent, ultrasonic cleaning with heated deionized water, and drying.
[0011] Preferably, the frequency of the organic solvent ultrasonic cleaning is 15 to 25 KHz.
[0012] Preferably, the frequency of the deionized water heated ultrasonic cleaning is 20-35 KHz, and the heating temperature of the deionized water heated ultrasonic cleaning is 50-80°C.
[0013] Preferably, the partial dezincification treatment comprises: mixing the pretreated copper-zinc alloy with an acid solution to perform a replacement reaction, and then sequentially performing weak alkaline solution washing, water washing and drying.
[0014] Preferably, the acid solution is one of a nitric acid solution, a sulfuric acid solution and a hydrochloric acid solution.
[0015] The present invention also provides a copper-zinc alloy catalyst prepared by the preparation method described in the above technical scheme.
[0016] The present invention also provides the use of the copper-zinc alloy catalyst described in the above technical solution in preparing low-carbon alcohols from synthesis gas, comprising the following steps:
[0017] After impurities are removed from the copper-zinc alloy catalyst, a reaction gas is introduced and reacted at a pressure of 3 to 5 MPa and a temperature of 240 to 340° C. to obtain a low-carbon alcohol.
[0018] Preferably, the flow rate of the reaction gas is 80-120 mL / min, and the volume space velocity is 9600-14400 h -1 ; The reaction gases are H2 and CO; the volume ratio of H2 and CO is (1~3):1.
[0019] The present invention provides a method for preparing a copper-zinc alloy catalyst, comprising the following steps: pre-treating copper-zinc alloy particles to obtain a copper-zinc alloy catalyst; or pre-treating copper-zinc alloy particles and then partially dezincifying them to obtain a copper-zinc alloy catalyst. The present invention uses copper-zinc alloy particles as a catalyst, and uses the CuZn alloy phase in the copper alloy as a catalytic active site to improve the catalytic performance of the copper-zinc alloy catalyst; by partially dezincifying the copper-zinc alloy, Zn in the alloy is partially removed, which expands the specific surface area of the particles and provides more active sites for catalyzing the synthesis of low-carbon alcohols from syngas, thereby achieving a good catalytic effect without using a carrier and an auxiliary agent. The results of the examples show that the copper-zinc alloy catalyst provided in the present application can achieve a CO conversion rate of 20.86% and a C 2+ The alcohol selectivity can reach 62.78%, which has good catalytic effect and C 2+ Alcohol selectivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a SEM image of the copper-zinc alloy catalyst prepared in Example 1 of the present invention, magnified 100 times;
[0021] Figure 2 This is a SEM image of the copper-zinc alloy catalyst prepared in Comparative Example 1 of the present invention, magnified 100 times;
[0022] Figure 3 This is a SEM image of the copper-zinc alloy catalyst prepared in Comparative Example 2 of the present invention, magnified 100 times;
[0023] Figure 4 The XRD spectra of the copper-zinc alloy catalysts prepared in Example 1 and Comparative Examples 1-2 of the present invention;
[0024] Figure 5 This is a SEM image of the copper-zinc alloy catalyst prepared in Example 1 of the present invention, magnified 5000 times;
[0025] Figure 6 This is a SEM image of the copper-zinc alloy catalyst prepared in Example 2 of the present invention, magnified 5000 times;
[0026] Figure 7 This is a SEM image of the copper-zinc alloy catalyst prepared in Example 3 of the present invention, magnified 5000 times;
[0027] Figure 8 This is a SEM image of the copper-zinc alloy catalyst prepared in Example 4 of the present invention, magnified 5000 times;
[0028] Fig. 9 This is a SEM image of the copper-zinc alloy catalyst prepared in Example 5 of the present invention, magnified 5000 times;
[0029] Fig.10 The XRD spectra of the copper-zinc alloy catalysts prepared in Examples 1 to 5 of the present invention;
[0030] Fig.11 The figure is a graph showing the CO conversion rate variation of the copper-zinc alloy catalyst in Application Example 1 of the present invention and Comparative Application Examples 1-2;
[0031] Fig.12 It is a graph showing the change in total alcohol selectivity of the copper-zinc alloy catalyst in Application Example 1 of the present invention and Comparative Application Examples 1-2;
[0032] Fig.13 C of the copper-zinc alloy catalyst in Application Example 1 of the present invention and Comparative Application Examples 1-2 2+ Alcohol percentage change chart. DETAILED DESCRIPTION
[0033] The present invention provides a method for preparing a copper-zinc alloy catalyst, comprising the following steps: pretreating copper-zinc alloy particles to obtain a copper-zinc alloy catalyst;
[0034] Alternatively, the copper-zinc alloy particles are pretreated and then partially dezincified to obtain a copper-zinc alloy catalyst.
[0035] In one technical solution of the present invention, the copper-zinc alloy particles are pretreated to obtain a copper-zinc alloy catalyst.
[0036] In another technical solution of the present invention, the copper-zinc alloy particles are pretreated and then partially dezincified to obtain a copper-zinc alloy catalyst.
[0037] In the present invention, the material of the copper-zinc alloy particles is preferably brass.
[0038] In the present invention, the brass is industrial brass powder containing only two elements, Cu and Zn. The present invention limits the material of the copper-zinc alloy particles to the above type, which is beneficial to the catalytic activity of the catalyst.
[0039] In the present invention, the pretreatment preferably comprises: sequentially subjecting the copper-zinc alloy particles to ultrasonic cleaning with an organic solvent, ultrasonic cleaning with heated deionized water, and drying.
[0040] In the present invention, the organic solvent ultrasonic cleaning is preferably acetone ultrasonic cleaning and ethanol ultrasonic cleaning performed sequentially; the number of acetone ultrasonic cleaning is preferably 2 times; the number of ethanol ultrasonic cleaning is preferably 2 times; the frequency of organic solvent ultrasonic cleaning is preferably 15-25KHz, more preferably 20KHz.
[0041] In the present invention, the number of times of the deionized water heated ultrasonic cleaning is preferably 3 times; the frequency of the deionized water heated ultrasonic cleaning is preferably 20 to 35 KHz, more preferably 30 KHz; the heating temperature of the deionized water heated ultrasonic cleaning is preferably 50 to 80°C, more preferably 60°C. The present invention does not specifically limit the operation of the organic solvent ultrasonic cleaning and the deionized water heated ultrasonic cleaning, and conventional ultrasonic operations of those skilled in the art can be used. The present invention can ensure more sufficient cleaning and remove impurities in the copper-zinc alloy particles by limiting the number and frequency of ultrasonic cleaning to the above range.
[0042] In the present invention, the drying temperature is preferably 90-120°C, more preferably 110°C; the drying time is preferably 10-15h, more preferably 12h. The present invention limits the drying temperature and time to the above ranges to ensure that the pretreated copper-zinc alloy particles are fully dried.
[0043] In the present invention, the partial dezincification treatment preferably comprises: mixing the pretreated copper-zinc alloy with an acid solution to carry out a replacement reaction, and then sequentially washing with a weak alkaline solution, washing with water and drying.
[0044] In the present invention, the acid solution is preferably one of nitric acid solution, sulfuric acid solution and hydrochloric acid solution, more preferably hydrochloric acid solution; the hydrochloric acid solution is preferably concentrated hydrochloric acid with a mass fraction of 36-38%. The present invention limits the concentration of the acid solution to the above range, which is conducive to the replacement reaction between the copper-zinc alloy and the acid solution.
[0045] In the present invention, the temperature of the replacement reaction is preferably room temperature; the time of the replacement reaction is preferably 1 to 36 hours, more preferably 12 to 36 hours, and further preferably 20 to 28 hours. The present invention limits the temperature and time of the replacement reaction to the above ranges to ensure that part of the zinc in the alloy is removed, increase the number of pores on the catalyst surface, and improve the catalytic performance of the catalyst.
[0046] In the present invention, the replacement reaction is preferably shaken after a certain time interval; the certain time interval is preferably 2 to 6 hours. The present invention can quickly remove bubbles generated by the reaction through shaking, thereby achieving the purpose of partially dezincifying the copper-zinc alloy.
[0047] In the present invention, the weak alkaline solution is preferably a sodium carbonate solution or a potassium carbonate solution, more preferably a potassium carbonate solution; the molar concentration of the weak alkaline solution is preferably 0.1 to 0.5 mol / L.
[0048] The present invention has no special restrictions on the weak alkaline solution washing and water washing operations, and the commonly used operations of those skilled in the art are adopted, and finally the filtrate is titrated with a silver nitrate solution to determine whether it does not contain Cl -The present invention uses a weak alkaline solution to clean and neutralize the residual acid on the catalyst surface, and then washes with water to remove other impurity ions on the surface of the copper-zinc alloy particles.
[0049] In the present invention, the drying temperature is preferably 90 to 120° C., more preferably 110° C. The present invention has no particular limitation on the drying time, as long as the washed copper-zinc alloy catalyst can be dried.
[0050] The present invention adopts copper-zinc alloy particles as catalysts and utilizes the CuZn alloy phase in the copper alloy as catalytic active sites to improve the catalytic performance of the copper-zinc alloy catalyst; by partially dezincifying the copper-zinc alloy, Zn in the alloy is partially removed, the specific surface area of the particles is expanded, and more active sites for catalyzing the synthesis of low-carbon alcohols from synthesis gas are provided, so that a good catalytic effect can be achieved without using a carrier and an additive.
[0051] The present invention also provides a copper-zinc alloy catalyst prepared by the preparation method described in the above technical solution.
[0052] The present invention also provides the use of the copper-zinc alloy catalyst described in the above technical solution in preparing low-carbon alcohols from synthesis gas, comprising the following steps:
[0053] After impurities are removed from the copper-zinc alloy catalyst, a reaction gas is introduced and reacted at a pressure of 3 to 5 MPa and a temperature of 240 to 340° C. to obtain a low-carbon alcohol.
[0054] In the present invention, the device for preparing low-carbon alcohols from synthesis gas is preferably a fixed bed reactor. In the present invention, the loading amount of the copper-zinc alloy catalyst is preferably 0.5 to 1.5 g, more preferably 1 g. In the present invention, setting the loading amount of the catalyst within the above range can be beneficial to the reaction of preparing low-carbon alcohols from synthesis gas.
[0055] In the present invention, the copper-zinc alloy catalyst is preferably placed in a quartz reaction tube first and then placed in a fixed bed reactor for reaction. The present invention can avoid the catalyst directly contacting the inner wall of the stainless steel tube in the fixed bed reactor by placing the copper-zinc alloy catalyst in the quartz reaction tube first.
[0056] In the present invention, N2 is introduced into the quartz reaction tube and then the temperature is raised to 300° C. for impurity removal. The present invention has no special restrictions on the flow rate of N2, the heating rate and the time of impurity removal, and the operation can be performed using parameters commonly used by those skilled in the art.
[0057] In the present invention, the flow rate of the reaction gas is preferably 80-120 mL / min, more preferably 100 mL / min; the space velocity of the reaction gas is preferably 9600-14400 h -1 , preferably 12000h-1 The reaction gases are preferably H2 and CO; the volume ratio of H2 to CO is preferably (1-3):1, more preferably 2:1. The present invention limits the flow rate, type and ratio of the reaction gas to the above range to better synthesize low-carbon alcohols.
[0058] In the present invention, the pressure of the reaction gas for reaction is 3-5MPa, preferably 4MPa; the temperature of the reaction gas for reaction is 240-340°C, preferably 300°C. In the present invention, the heating rate of the temperature rise to the reaction temperature is preferably 2°C / min. The present invention limits the reaction pressure and temperature to the above ranges to ensure better reaction and improve the conversion rate of synthesis gas.
[0059] After the reaction is completed, the product of the reaction is preferably separated into a gas phase and a liquid phase by circulating condensation, and the gas phase and liquid phase products are quantitatively analyzed by chromatography.
[0060] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0061] Example 1
[0062] Put 5g of brass particles into a beaker, add 25mL of acetone and perform ultrasonic washing at room temperature for 30 minutes, then repeat the ultrasonic washing with acetone once, then replace acetone with anhydrous ethanol, perform ultrasonic washing twice, each time for 30 minutes, the ultrasonic frequency is 20KHz, and then wash with deionized water for 3 times, the ultrasonic frequency is 30KHz. After washing, put the brass particles into an oven, bake at 110℃ for 12h, and then take out for use to obtain a copper-zinc alloy catalyst, recorded as Cu-ye.
[0063] Comparative Example 1
[0064] The difference between Comparative Example 1 and Example 1 is that the brass particles are replaced by copper particles, and the rest is the same as Example 1. The obtained copper-zinc alloy catalyst is denoted as Cu-pu.
[0065] Comparative Example 2
[0066] The difference between Comparative Example 2 and Example 1 is that the brass particles are replaced by bronze particles, and the rest is the same as Example 1. The obtained copper-zinc alloy catalyst is denoted as Cu-cy.
[0067] Example 2
[0068] The copper-zinc alloy catalyst obtained in Example 2 was placed in a small beaker containing 15 mL of concentrated hydrochloric acid (36-38%), and reacted at room temperature for 12 h for partial dezincification, wherein the catalyst was shaken once every 2 h to remove bubbles on the surface as quickly as possible. After the reaction time was over, it was first washed twice with the prepared 0.2 mol / L sodium carbonate until neutral, and then the excess impurity ions on the catalyst surface were washed with deionized water, and dried at 110°C for use to obtain a copper-zinc alloy catalyst, recorded as Cu-ye-12h.
[0069] Example 3
[0070] The only difference between Example 3 and Example 2 is that the reaction time of the partial dezincification treatment is 20 hours, and the reaction is shaken every 4 hours. The other conditions are the same as those of Example 2. The obtained copper-zinc alloy catalyst is denoted as Cu-ye-20h.
[0071] Example 4
[0072] The difference between Example 4 and Example 2 is that the reaction time of the partial dezincification treatment is 28 hours, and the reaction is shaken every 6 hours. The other conditions are the same as those of Example 2. The obtained copper-zinc alloy catalyst is recorded as Cu-ye-28h.
[0073] Example 5
[0074] The only difference between Example 5 and Example 2 is that the reaction time of the partial dezincification treatment is 36 hours, and the reaction is shaken every 6 hours. The other conditions are the same as those of Example 2. The obtained copper-zinc alloy catalyst is denoted as Cu-ye-36h.
[0075] Application Example 1 and Comparative Application Examples 1-2
[0076] The copper-zinc alloy catalyst prepared in Example 1 and Comparative Examples 1-2 was applied to the synthesis of low-carbon alcohols from synthesis gas. A fixed bed reactor was used for the reaction. The copper-zinc alloy catalyst was placed in a quartz reaction tube with a catalyst loading of 1 g. The temperature was raised to 300°C at a heating rate of 2°C / min for 3 h in a N2 (100 mL / min) atmosphere for impurity removal. After the temperature was cooled to room temperature, the synthesis gas was directly switched to be pressurized to 4 MPa and reacted at 240-340°C. The heating rate to the reaction temperature was 2°C / min. The synthesis gas composition was H2 and CO. The volume ratio of H2 to CO was 2:1. The total gas flow rate was 100 mL / min and the reaction space velocity was 12000 h -1 After 2 hours of reaction, the reaction products were divided into gas phase and liquid phase by circulating condensation, and the gas phase and liquid phase products were quantitatively analyzed by chromatography.
[0077] Application Examples 2 to 5
[0078] The copper-zinc alloy catalyst prepared in Examples 2 to 5 was applied to the preparation of low-carbon alcohols from synthesis gas. A fixed bed reactor was used for the reaction. The copper-zinc alloy catalyst was placed in a quartz reaction tube with a catalyst loading of 1 g. The temperature was raised to 300°C at a heating rate of 2°C / min for 3 h in a N2 (100 mL / min) atmosphere for impurity removal. After cooling to room temperature, the reaction was directly switched to synthesis gas at 4 MPa and 300°C. The heating rate to the reaction temperature was 2°C / min. The synthesis gas composition was H2 and CO. The volume ratio of H2 to CO was 2:1. The total gas flow rate was 100 mL / min and the reaction space velocity was 12000 h -1 After 2 hours of reaction, the reaction products were divided into gas phase and liquid phase by circulating condensation, and the gas phase and liquid phase products were quantitatively analyzed by chromatography.
[0079] Comparative Application Example 3
[0080] The catalyst used in comparative application example 3 is the catalyst Cat-4 of Example 4 for catalyzing the synthesis gas to alcohol using the electrolytic brass product as a catalyst disclosed in patent application number 201711158742.7. The catalyst dosage is 0.5 g. Before the reaction, the mixture is reduced at 470°C with a volume ratio of 6:1 H2 / N2 mixed gas for 6 hours, and then the reactor temperature is reduced to 450°C for reaction. Other operations are the same as those in application example 2.
[0081] The present invention uses an electron microscope to observe the morphology of the copper-zinc alloy catalyst;
[0082] XRD ray diffractometer was used to characterize the phase of copper-zinc alloy catalyst;
[0083] Haixin GC950 chromatograph was used to carry out chromatographic quantitative analysis on the products obtained from the application of catalyst in the preparation of low-carbon alcohols from synthesis gas.
[0084] Figures 1 to 3 The SEM images of the copper-zinc alloy catalysts prepared in Example 1 and Comparative Examples 1-2 are magnified 100 times. Figures 1 to 3 It can be seen that the Cu-ye catalyst is irregular in shape, while the Cu-pu and Cu-cy catalysts are both relatively smooth spherical.
[0085] Figure 4 The XRD spectra of the copper-zinc alloy catalysts prepared in Example 1 and Comparative Examples 1-2 are shown in FIG. Figure 4 It can be seen that the Cu-ye catalyst contains only the Cu5Zn8 alloy phase, the Cu-pu catalyst shows the Cu phase and the Zn phase, and the Cu-cy catalyst contains the Cu phase and the Cu 41 Sn 11 Alloy phase.
[0086] Figures 5 to 9The SEM images of the copper-zinc alloy catalysts prepared in Examples 1 and 2 to 5 are magnified 5000 times. Figures 5 to 9 It can be seen that the number of pores on the catalyst surface increases after dezincification treatment.
[0087] Fig.10 The XRD spectra of the copper-zinc alloy catalysts prepared in Examples 1 to 5 show that the Cu-ye catalyst that has not been dezincified has only the Cu5Zn8 alloy phase. During the reaction with hydrochloric acid, Zn is partially removed. As the removal time increases, the peak of the Cu5Zn8 alloy phase gradually decreases, and the Cu phase peak gradually becomes sharper. After part of the Zn is removed, the Cu5Zn8 alloy and Cu coexist in the catalyst.
[0088] The specific surface area, pore volume and pore diameter of the copper-zinc alloy catalysts prepared in Examples 1 to 5 were tested. The test results are shown in Table 1.
[0089] Table 1 Specific surface area, pore volume and pore diameter of the copper-zinc alloy catalysts prepared in Examples 1 to 5
[0090] catalyst <![CDATA[Specific surface area / (m 2 ·g -1 )]]> <![CDATA[Pore volume / (cm 3 ·g -1 )]]> Average pore size / nm Cu-ye 0.47 0.11 3.40 Cu-ye-12h 0.79 0.18 15.29 Cu-ye-20h 1.00 0.23 17.52 Cu-ye-28h 1.21 0.28 21.12 Cu-ye-36h 1.86 0.43 23.85
[0091] It can be seen from Table 1 that the specific surface area, pore volume and pore diameter of the copper-zinc alloy catalysts prepared in Examples 2 to 5 increased after partial dezincification treatment.
[0092] The CO conversion rate change, total alcohol selectivity change and C 2+ The change of alcohol percentage is shown in the figure Figures 11 to 13 As shown, from Figures 11 to 13 It can be seen that the CO conversion rate of the copper-zinc alloy catalyst increases with the increase of reaction temperature, while the selectivity of total alcohol decreases. 2+ The proportion of alcohol in the total alcohol increased and gradually stabilized at around 54%.
[0093] The activity evaluation results of the copper-zinc alloy catalysts prepared in Application Example 1 and Comparative Application Examples 1-2 at 300°C are shown in Table 2.
[0094] Table 2 Activity evaluation results of the copper-zinc alloy catalysts prepared in Application Example 1 and Comparative Application Examples 1-2 at 300°C
[0095]
[0096] It can be seen from Table 2 that the catalyst containing only CuZn alloy can also synthesize low-carbon alcohols. Compared with the Cu-ye catalyst, the Cu-pu catalyst does not have an alloy phase and has the worst catalytic effect. The CO conversion rate of the catalyst is low, and the C 2+Although the Cu-cy catalyst contains a CuSn alloy phase, its catalytic activity is significantly reduced compared to the CuZn alloy phase. Therefore, the copper-zinc alloy catalyst containing the CuZn alloy phase has a better catalytic effect.
[0097] The activity evaluation results of Application Examples 1 to 5 and Comparative Application Example 3 are shown in Table 3.
[0098] Table 3 Activity evaluation results of application examples 1 to 5 and comparative application example 3
[0099]
[0100] Table 3 shows the activity evaluation results of Application Examples 1 to 5 and Comparative Application Example 3. Compared with the catalyst (Cu-ye) in Application Example 1, the conversion rates of the catalysts in Application Examples 2 to 5 are all increased, the total alcohol selectivity is increased, and the alcohol yield is greatly increased, indicating that the catalytic performance can be improved after dezincification treatment; Compared with the Cat-4 catalyst in Application Example 3, the Cat-4 catalyst needs to be reduced at a higher temperature for 6 hours (the present invention does not need to be reduced, and Comparative Example 3 is reduced at 470°C), and the CO conversion rate of the catalyst only reaches 41.2% when reacting at a higher temperature (the present invention reacts at 300°C, and Comparative Example 3 reacts at 450°C), but the C in the product of the comparative catalyst is 1.3%. 2+ The proportion of alcohol is only 25.7%. Even at 450°C, the carbon chain growth effect is not good. On the contrary, the catalyst of the present invention has a good C 2+ Alcohol selectivity, C 2+ Alcohol accounts for the highest proportion of 62.78%.
[0101] The copper-zinc alloy catalyst provided by the present invention can achieve a CO conversion rate of 20.86% when using only the copper-zinc alloy catalyst. 2+ The alcohol selectivity can reach 62.78%, which has good catalytic effect and C 2+ Alcohol selectivity has better industrial prospects.
[0102] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. An application of a copper-zinc alloy catalyst in preparing low-carbon alcohols from synthesis gas, comprising the following steps: After removing impurities from the copper-zinc alloy catalyst, a reaction gas is introduced to react at a pressure of 3-5 MPa and a temperature of 240-340° C. to obtain a low-carbon alcohol; the reaction gas is H2 and CO; The preparation method of the copper-zinc alloy catalyst comprises the following steps: The copper-zinc alloy particles are pretreated and then partially dezincified to obtain a copper-zinc alloy catalyst; The partial dezincification treatment comprises: mixing the pretreated copper-zinc alloy with an acid solution to carry out a replacement reaction, and then washing with a weak alkaline solution, washing with water and drying in sequence; The acid solution is a concentrated hydrochloric acid solution with a mass fraction of 36-38%; The replacement reaction time is 28 to 36 hours.
2. The use according to claim 1, characterized in that: The copper-zinc alloy particles are made of brass.
3. The use according to claim 1, characterized in that: The pretreatment comprises: sequentially performing organic solvent ultrasonic cleaning, deionized water heated ultrasonic cleaning and drying on the copper-zinc alloy particles.
4. The use according to claim 3, characterized in that: The frequency of the organic solvent ultrasonic cleaning is 15-25 KHz.
5. The use according to claim 3, characterized in that: The frequency of the deionized water heated ultrasonic cleaning is 20-35KHz, and the heating temperature of the deionized water heated ultrasonic cleaning is 50-80°C.
6. The use according to claim 1, characterized in that: The flow rate of the reaction gas is 80-120 mL / min, and the volume space velocity is 9600-14400 h -1 ; The volume ratio of H2 and CO is (1~3):1.
Citation Information
Patent Citations
Preparation method of catalyst for using synthetic gas to prepare low-carbon alcohol
CN107899576A
Sheet type copper-zinc alloy powder promoter
CN102962072A
CuZn catalyst for preparing ethanol through CO hydrogenation as well as preparation method and application of CuZn catalyst
CN113522296A